Mapping habitat protection priority over a marine ecoregion under information gaps. Issue 2 (6th November 2020) - Wang, Xianyan; Kittiwattanawong, Kongkiat; Junchompoo, Chalatip; Sakornwimon, Watchara; Chen, Mo; Wu, Fuxing; Jutapruet, Suwat; Huang, Shiang‐Lin
Abstract: Aim: Holistic marine biodiversity conservation refers to ecosystem‐based management through marine conservation planning (MCP), based on mapping habitat protection priority areas. In practice, MCP is frequently hindered by information gaps in biodiversity distributions, particularly on a marine ecoregion scale. Species distribution modelling (SDM) can help to resolve this gap and provide information essential for MCP scenarios. We constructed habitat configurations for three coastal marine megafauna animals using SDM, then based MCP scenarios on the projected habitat configurations and tested the use of marine megafauna animals as surrogates to protect major ecosystems. Location: Gulf of Thailand, Southeast Asia. Methods: A MaxEnt model was used to project likely habitats for Indo‐Pacific humpback dolphins ( Sousa chinensis ), Irrawaddy dolphins ( Orcaella brevirostris ) and sea turtles in the Gulf of Thailand. MARXAN software was used to prioritize spatial configurations for habitat protection. The percentage of overlaps between MARXAN delineations and major biodiversity features in the Gulf of Thailand were calculated. Results: Habitat configurations of humpback dolphins, Irrawaddy dolphins and sea turtles were projected throughout the coastal and estuarine waters along the Gulf of Thailand. MCP based on the habitat of three marine megafauna animals highlighted five critical habitats for the protection of major ecosystems in the Gulf of Thailand. Main conclusions: Holistic MCP starts with mapping critical habitats for marine protected area (MPA) networks, balances MPA networks with maritime livelihood activities and alleviates conflicts between MPA management and local livelihood needs. A combination of SDM and MARXAN methods provides a cost‐effective approach to delineate MPA networks. In this approach, surrogate selection and data preparation should consider niches representative of regional ecosystem features and avoid spatial sampling bias. In coastal and estuarine waters, marine megafauna such as coastal cetaceans and sea turtles may serve as efficient surrogates to protect major ecosystems.